Dynamic interactions between lumbar intervertebral motion segments during forward bending and return. (26th March 2020) - Breen, Alexander; Breen, Alan
Abstract: Continuous dynamic multi-segmental studies of lumbar motion have added depth to our understanding of the biomechanics of back pain, but few have attempted to continuously measure the proportions of motion accepted by individual levels. This study attempted to compare the motion contributions of adjacent lumbar levels during an active weight bearing flexion and return protocol in chronic, non-specific low back pain (CNSLBP) patients and controls using quantitative fluoroscopy (QF). Eight CNSLBP patients received QF during guided standing lumbar flexion. Dynamic motion sharing of segments from L2 to S1 were calculated and analysed for interactions between levels. Eight asymptomatic controls were then matched to the 8 patients for age and sex and their motion sharing patterns compared. Share of intersegmental motion was found to be consistently highest at L2-L3 and L3-L4 and lowest at L5-S1 throughout the motion in both groups, with the exception of maximum flexion where L4-L5 received the greatest share. Change in motion sharing occurred throughout the flexion and return motion paths in both participant groups but tended to vary more at L4-L5 in patients (p < 0.05). In patients, L5-S1 provided less angular range (p < 0.05) and contributed less at maximum bend (p < 0.05), while L3-L4, on average over the bending sequence, provided a greater share of motion (p < 0.05). Intervertebral motion sharing inequality is therefore a normal feature during lumbar flexion. However, in patients, inequality was more pronounced, and variability of motion share at some levels increased. These effects may result from differences in muscular contraction or in the mechanical properties of the disc.